Effect of weed control on the performance of transplant BRRI Dhan 32 (Progressive Agriculture, 2018)
A field experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July to December 2003 to find out the effect of weed control on the performance of transplant Aman rice cv. BRRI Dhan 32. Weed control treatments  Included in the study were no weeding, one hand weeding, two hand weeding, one hand weeding+one weeding with Japanese rice weeder, Rift@ 0.5, 0.75, 1.0,  and 1.25 L ha-1 and Rostar@ 1.0, 1.5, 2.0, and 2.5 L ha-1. Important weed species found to infest the crop were Angta (Panicum repens), Acidgras (Ammania bacifera L.) Nackphulee (Cyperous difformis), Khudeshama (Echinochloa crusgalli) was the least important weed species. Higher doses of Rift 1.25L ha-1 and Ronstar 2.5 L ha-1 showed the best performance in reducing weed density and weed dry weight. The highest grain yield (5.0 4ton ha-1) was obtained from Ronstar 2.0 L ha-1 which was identical with the second highest grain yield (4.93 t ha-1) obtained from Rift 1.0 L ha-1. The highest net income of tk. 38915 ha-1 was obtained from Ronstar 2.0 L ha-1 and the next highest from Rift 1.0L ha-1.Progressive Agriculture 28 (4): 271-278, 2017